New insights on the effects of ionic liquid structural changes at the gene expression level: Molecular mechanisms of toxicity in Daphnia magna - Jeremias, Guilherme (2020)
Knowledge on the molecular basis of ionic liquids' (ILs) ecotoxicity is critical for the development of these designer solvents as their structure can be engineered to simultaneously meet functionality performance and environmental safety. The molecular effects of ILs were investigated by using RNA-sequencing following Daphnia magna exposure to imidazolium- and cholinium-based ILs: 1-ethyl-3-methylimidazolium chloride ([C2mim]Cl), 1-dodecyl-3-methylimidazolium chloride ([C12mim]Cl) and cholinium chloride ([Chol]Cl)-; the selection allowing to compare different families and cation alkyl chains. ILs shared mechanisms of toxicity focusing e.g. cellular membrane and cytoskeleton, oxidative stress, energy production, protein biosynthesis, DNA damage, disease initiation. [C2mim]Cl and [C12mim]Cl were the least and the most toxic ILs at the transcriptional level, denoting the role of the alkyl chain as a driver of ILs toxicity. Also, it was reinforced that [Chol]Cl is not devoid of environmental hazardous potential regardless of its argued biological compatibility. Unique gene expression signatures could also be identified for each IL, enlightening specific mechanisms of toxicity.